(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2023)
The game of permutations with repetitions in ‘Doppio Sempione’ by Elio Vittorini A careful research and exploration of Vittorini Collection (Centro Apice, Archivi della Parola, dell’Immagine e della Comunicazione Editoriale – Milano) has brought to light the remaking, for a new publication, of a passage from the novel Il Sempione strizza l’occhio al Frejus by Elio Vittorini (Bompiani 1947). The contribution analyses Vittorini’s writing process which, after a research on all the versions of the manuscripts, can be defined as a ‘game of permutations with repetitions’.